ANALISIS KEBIJAKAN PENGENDALIAN URBANISASI KOTA BERASTAGI KABUPATEN KARO SUMUT - Putri Anne Br Sembiring; Matius Bangun (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2021)
ABSTRAK This study aims at analyzing the factors driving and pulling the occurrence of urbanization in Berastagi and the efforts made by the Karo district government to control it. The method used is descriptive qualitative with primary data sources from interviews and field observations, while secondary data is from literary studies, social media and documentation. The data analysis used is the Delphi analysis to equalize the perceptions of the informants, the analysis of pull and support factors as well as policy analysis on efforts to control urbanization in the City of Berastagi.The conclusion from the results of this study is that the main driving factor for urbanites from their hometowns for those who are not married is shy to live in the village, while for those who are already married are limited employment opportunities in the village. The main draw factor for urbanites from the destination area is for those who do not have family, invite friends who are already in the city while those who are already married are looking for a new job. Efforts made by the Government in the Origin Region are Encouraging and Facilitating: Soft Loans, MSME Empowerment Program Assistance (especially Micro Enterprises) and Building Village Facilities through APBD. Efforts made by the Government in the urbanization destination of Berastagi City are to make a new settlement plan consisting of a. Agricultural Zone on Jl. Air (Column Monument towards Simpang Empat District); b. Office Zone On Jl. Djamin Ginting (from Tugu Kol to Kec. Kaban Jahe); . and c. Tourism Zone Jl. Djamin Ginting starting from the monument mejuah Juah towards Tahura).